PENGARUH METODE KARYAWISATA (FIELD TRIP) TERHADAP KEMAMPUAN MENULIS TEKS PUISI PADA SISWA KELAS X SMK NEGERI 2 KARAWANG TAHUN AJARAN 2017/2018 - Devy Permatasari; Wikanengsih Wikanengsih (IKIP Siliwangi, 2019)
This study aims to explain the influence of field trip method in learning to write poetry text on class X student of Administration Office 2 SMK Negeri 2 Karawang. The population in this study is all students of class X Administration Office 2 SMK Negeri 2 Karawang with the number of 50 students. The sample in this study amounted to 25 students taken at random simple with random sampling. The instrument used to collect data is the assignment of essay writing essay writing poetry. The method used in this research is the experimental method. Hypothesis testing is done by using